Federation of 5G services using distributed ledger technologies†. Issue 6 (20th July 2020) - Antevski, Kiril; Bernardos, Carlos J.
Abstract : Federation of services, as a 5G networks concept, aims to provide orchestration of services across multiple administrative domains. In this paper, we are exploring a solution of applying distributed ledger technologies, precisely the combination of blockchain and smart contracts, to enable highly secure, private, fast and distributed interaction between administrative domains in the federation process. Along with the designed solution, we developed an experimental prototype that requires simple one‐time setup and fast simultaneous registration time for multiple administrative domains. Obtained results show single service federation times (without considering the deployment time) of around 5 seconds. Abstract : Federation of services, as a 5G networks concept, aims to provide orchestration of services across multiple administrative domains. Distributed ledger technologies are applied to enable secure, private, fast and distributed interaction between administrative domains in the federation process. Through an experimental prototype that requires simple setup and fast simultaneous registration time for multiple administrative domains, we obtained results where single service federation takes around 5 seconds (without the deployment time).